When Uniform Standards Are Missing: Judicial Inconsistency in Wages During Termination Proceedings in Indonesia - Hayati, Tri; Uwiyono, Aloysius; Fitriana, Fitriana (The Indonesian Journal of Socio-Legal Studies, 2026)
This article examines how courts lack uniform judicial standards for determining Upah Proses, which refers to wages payable during termination proceedings in Indonesia. Constitutional Court Decision No. 37/PUU-IX/2011 requires employers to pay Upah Proses until courts issue a final and binding judgment. However, subsequent instruments introduce conflicting limitations and ambiguous provisions, including Supreme Court Circular Letter No. 3 of 2015 and Law No. 6 of 2023. Such inconsistencies create normative disharmony across constitutional, statutory, and administrative frameworks. The absence of coherent interpretive guidance divides the judiciary, leading courts to issue divergent rulings, even in cases with similar factual circumstances. The study examines 117 judicial decisions issued between 2007 and 2023, and analyzes eight representative findings. Interviews with workers and employers show how legal uncertainty impacts the parties involved. The findings show that ad hoc judges, representing worker and employer constituencies, adopt differing orientations that further exacerbate the absence of standardized judicial criteria. This fragmentation in judicial reasoning increases workers’ socio-economic vulnerability during protracted litigation. The article advocates for the urgent harmonization of legal norms and clarification of judicial guidelines. Such measures would enhance legal certainty, promote consistent adjudication, and provide stronger protection for workers, who are the structurally weaker party within Indonesia’s industrial relations system.